A road map to vocational education and training in industrialized countries - Eichhorst, Werner [Verfasser]; Rodriguez-Planas, Núria [Verfasser]; Schmidl, Ricarda [Verfasser]; Zimmermann, Klaus F. [Verfasser] (My University, 2015)
"Young people have been among those most affected by the recent financial crisis. Vocational education and training (VET) is often viewed as the silver bullet for the youth joblessness problem. In this article, the authors provide a better understanding of VET in industrialized countries, proposing a typology with three types of vocational systems: 1) vocational and technical schools, 2) formal apprenticeships, and 3) dual apprenticeship systems that combine school training with a firm-based approach. They first describe the strengths and challenges of each system. They subsequently review the evidence of the effectiveness of VET versus general education and the relative effectiveness of the different VET systems. Results indicate that VET is a valued alternative beyond the core of general education and that the use of apprenticeships combined with institutional learning tends to be more effective than school-based VET." (Authors' abstract, BIBB-Doku)
Keywords: S System beruflicher Bildung; S 1.3 Berufliche Erstausbildung; S 4.3.3 Effizienz & Effektivität des Berufsbildungswesens; I 2.2 Europa; I 2.3.2 Nordamerika; I 2.3.5 Australien, Ozeanien; Berufsbildungssystem; Berufsausbildung; Schulische Berufsausbildung; Betriebliche Berufsausbildung; Effektivität; Internationaler Vergleich; Industrieländer; Europa; USA; Australien